The futures of social practices of interaction between humans and Virtual Deceased Individuals : A Causal Layered Analysis of four ideal types - Hurtado Hurtado, Joshua (My University, 2020)
Research on digital immortality has identified thanatechnologies which facilitate the endurance of the presence of the deceased in the world of the living. One of these, the Virtual Deceased Individual (VDI), is the focus of the thesis. Due to the current limitations of digital technologies in generating a software that convincingly simulates being a deceased person, adopting a Futures Studies approach to the examination of the VDI and human interaction with it is helpful in understanding how future digital technologies might transform how human beings relate to mortality and mourn the deaths of others. Thirteen long interviews with participants of diverse ages and cultural backgrounds were conducted, and Causal Layered Analysis was used to construct four different images of the future (Ambivalence, Restoration, Concealment and Autonomy) which contrasted processes of relating to death and going through mourning according to the characteristics of the social practices focused on Human-VDI interaction. The images of the future reveal that the meanings assigned to the VDI and the role it plays in death acceptance and mourning processes are shaped by discourses on mortality and immortality, as well as by underlying metaphors of personhood. This suggests that for death acceptance and successful mourning to occur, social practices of Human-VDI interaction should encourage acknowledgement of loss.
Keywords: Virtual Deceased Individual, Death, Mourning, Social Practices, Causal Layered Analysis, Digital Immortality